The Effect of Updating the Local Pheromone on ACS Performance using Fuzzy Logic - Abdellatif El Afia; Safae Bouzbita; Rdouan Faizi (Institute of Advanced Engineering and Science, 2017)
Fuzzy Logic Controller (FLC) has become one of the most frequently utilised algorithms to adapt the metaheuristics parameters as an artificial intelligence technique. In this paper, the ???? parameter of Ant Colony System (ACS) algorithm is adapted by the use of FLC, and its behaviour is studied during this adaptation. The proposed approach is compared with the standard ACS algorithm. Computational results are done based on a library of sample instances for the Traveling Salesman Problem (TSPLIB).